Flavor anomalies, the diphoton excess and a dark matter candidate - Bauer, Martin; Neubert, Matthias (Arxiv, 2016)
We argue that the diphoton excess recently reported by ATLAS and CMS can be explained, along with several anomalies seen in the flavor sector, in models where a Standard-Model singlet scalar resonance with mass ≈ 750$ GeV is produced in gluon fusion via loops containing a scalar color- triplet leptoquark $φ$. For a leptoquark mass $M_φ \lesssim$ 1 TeV, the production cross section is naturally in the 10 fb range. A large → γ γ$ branching ratio can be obtained by coupling the scalar S to new color-singlet fermions $χ$ with electroweak scale masses, which can be part of an $SU(2)_L$ multiplet, whose neutral component has the right mass and quantum numbers to be a dark matter candidate. Our model reveals a connection between flavor anomalies, the nature of dark matter and a new scalar, which acts as a mediator to the dark sector. The loop-mediated decay → τ^+τ^-$ could be a striking signature of this model.
Gesehen am 10.01.2018